MBSR for Better Health: A Narrative Review - Mabel Gupta (International Journal of Behavioral Sciences, 2026)
Introduction: MBSR is a mindfulness-based intervention created by John Kibbat Zinn in the 1970's using the principles of the Buddhist tradition. Since its creation it has found to be effective in various physiological and psychological issues such as cardiovascular diseases, diabetes, blood pressure, hypertension, anxiety, depression, and other ailments. In this particular narrative review, we screened and selected various studies that observed better physiological and psychological health post the MBSR intervention. Methodology: PubMed and DOAJ were used to do literature review. 10 researches were included in this narrative analysis after pertinent papers were screened and selected using predetermined inclusion and exclusion criteria. The analysis was conducted on basis of their methodology, results, conclusions and limitations. Results: Studies have time and again have observed the positive changes associated with the MBSR intervention, for example: participants observed an improvement in overall health, mental health, life satisfaction, level of perceived stress etc., along with a pattern of decrement in negative factors is also observed such as a decrement in symptoms experienced related to disorders like anxiety and depression, somatic complaints etc. Conclusion: Post MBSR intervention scores of physiological and psychological related symptoms or ailments have been observed to be largely positive in comparison to the pre-intervention scores. Thus, we can conclude that the intervention is effective in improving an individual’s quality of life and life satisfaction if adopted as a wellness practice.
Keywords: MBSR; Mental health intervention; Physiological health; Stress reduction; psychological well-being; resilience